2010
DOI: 10.7202/039529ar
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Work-Family Balance: Are Family-Friendly Organizations More Attractive?

Abstract: Tous droits réservés © Département des relations industrielles de l'Université Laval, 2009Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. Résumé de l'article Dans un contexte de rareté de main-d'oeuvre, les organisations sont soumises à des pressions grandissantes pour attirer des employés de talents. Se préoccupant de leur capacité d'attraction, notamment au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 50 publications
(90 reference statements)
1
27
0
2
Order By: Relevance
“…Given the large population of working women in the labour market, as well as the fast growing number of both dual-career families and single-parent families, the need for balancing work-family responsibilities has become a growing challenge for many employees (Bourhis and Mekkaoui, 2010). The results for gender corroborated previous research and are instructive in designing total rewards packages that are relevant for the increasing numbers and needs of working women.…”
Section: Outline Of the Resultssupporting
confidence: 74%
“…Given the large population of working women in the labour market, as well as the fast growing number of both dual-career families and single-parent families, the need for balancing work-family responsibilities has become a growing challenge for many employees (Bourhis and Mekkaoui, 2010). The results for gender corroborated previous research and are instructive in designing total rewards packages that are relevant for the increasing numbers and needs of working women.…”
Section: Outline Of the Resultssupporting
confidence: 74%
“…Such efforts are aimed at improving organizational reputation among a variety of stakeholders so as to positively infl uence stakeholders' choices vis-à-vis the organization (Rindova, Williamson, Petkova, & Sever, 2005, p. 1033. In fact, there is growing evidence that positive reputations translate into a competitive advantage in terms of recruiting and retaining workers and building a diverse customer base (Bourhis & Mekkaoui, 2010;Cook & Glass, 2009;Greening & Turban, 2000;Hannon & Milkovich, 1996;Sen & Bhattacharya, 2001;Stevens, Plaut, & Sanchez-Burks, 2008). Several scholars suggest that a positive reputation is also directly linked to the perceived legitimacy of a fi rm (Arthur, 2003;Yang & Konrad, 2011).…”
Section: Diversity Efforts and Performancementioning
confidence: 99%
“…Recently, it has been reported that excessive demands of a role prevent attention to other roles, generating discomfort and dissatisfaction (Demerouti, Peeters, & van der Heijden, 2012). In organizations characterized by HRMP oriented to the external market, the effort put into conquering new customers would take away energy from the employee when attempting to devote attention to his personal and family needs (Bourhis & Mekkaoui, 2010), so it would be expected for them experience lower levels of satisfaction with their work. Based on such considerations it was assumed: H2: workers of companies whose HRMP are oriented to the results, to rigid systems, or to external markets, will experience less job satisfaction.…”
Section: Hrmp and Employees Job Satisfactionmentioning
confidence: 99%